Influence of Team Management Practices on Performance of Community-Based Projects in Embu County, Kenya - Nicasio Gicovi, Njue,; John Rugendo, Chandi, (European Scientific Journal, ESJ, 2019)
The purpose of this study was to examine the influence of team management practices (team formation, team motivation, team communication and team dispute resolution) on the performance of community-based projects in Embu, Kenya. Appropriate research hypothesis was derived from the substantive objective. Descriptive-correlational survey design was used to implement the research inquiry. The target population was 34 community-based projects in being implemented in Embu County. A sample of 32 projects was arrived at using Krejcie and Morgan table of sample determination. Proportionate stratified random sampling was used to select 32 project team leaders. Appropriate data was garnered using structured questionnaires. Data were analyzed using descriptive and inferential statistics. The results suggest that at F (1,156) =4.934, P=0.000<0.05 implying that at 95% the relationship was statistically significant. The correlation coefficient (R=0.653) showed that there exists strong positive correlation between team management practices and performance community-based projects. The coefficient of determination (R2=0.426) implied that team management practices explained 42.6% of performance of community-based projects. The findings have immense contribution to both knowledge and practice in the areas of team management practices and performance of community-based projects. Follow up studies should focus on testing similar variables across different project set-ups while triangulating different methodologies in order to derive more generalizable results.